ChemInform Abstract: Reactions of an Isolable Dialkylsilylene with Aromatic Nitriles Providing a New Type of Heterosilole. Issue 8 (25th February 2014) - Wang, Liliang; Chen, Weifeng; Li, Zhifang; Xiao, Xu‐Qiong; Lai, Guoqiao; Liu, Xupeng; Xu, Zheng; Kira, Mitsuo
Abstract The reaction of silylene (I) with aromatic nitriles bearing electron‐donating substituents on the phenyl ring (II) leads to the desired 1, 4‐diaza‐2‐siloles (III), whilst the reaction with aromatic nitriles with strong electron‐withdrawing substituents (IV) affords 1, 3‐diaza‐2‐siloles (V).